Case study research : design and methods. - Yin, Robert K., 1941- (Los Angeles : SAGE, 2009)
Providing a complete portal to the world of case study research, the Fourth Edition of Robert K. Yin's bestselling text Case Study Research offers comprehensive coverage of the design and use of the case study method as a valid research tool. This thoroughly revised text now covers more than 50 case studies (approximately 25% new), gives fresh attention to quantitative analyses, discusses more fully the use of mixed methods research designs, and includes new methodological insights. The book's coverage of case study research and how it is applied in practice gives readers access to exemplary case studies drawn from a wide variety of academic and applied fields. Key Features of the Fourth Edition * Highlights each specific research feature through 44 boxed vignettes that feature previously published case studies * Provides methodological insights to show the similarities between case studies and other social science methods * Suggests a three-stage approach to help readers define
The initial questions they will consider in their own case study research *Covers new material on human subjects protection, the role of Institutional Review Boards, and the interplay between obtaining IRB approval and the final development of the case study protocol and conduct of a pilot case * Includes an overall graphic of the entire case study research process at the beginning of the book, then highlights the steps in the process through graphics that appear at the outset of all the chapters that follow * Offers in-text learning aids including "tips" that pose key questions and answers at the beginning of each chapter, practical exercises, endnotes, and a new cross-referencing tableInhoudsopgave 1. Introduction : how to know whether and when to use case studies as a research method 2. Designing case studies : identifying your case(s) and establishing the logic of your case study 3. Preparing to collect case study evidence : what you need to do before starting to collect case
Study data 4. Collecting case study evidence : the principles you should follow in working with six sources of evidence 5. Analyzing case study evidence : how to start your analysis, your analytic choices, and how they work 6. Reporting case studies : how and what to compose
Keywords: Sociaal-wetenschappelijk onderzoek; Social casework